Development of microsatellites for the cacao frosty pod rot pathogen, Moniliophthora roreri. Issue 4 (26th July 2014) - Melo, B. L. B.; de Souza, J. T.; Santos, R. M. F.; Rehner, S. A.; Solis, K. H.; Suarez, C.; Hebbar, P. K.; Lemos, L. S. L.; Gramacho, K. P.; Roux, Jolanda
Summary Moniliophithora roreri, causal agent of cacao frosty pod rot, is considered one of the most devastating pathogens of this crop. In this study, we report the development of and validation of 28 microsatellite loci from an enriched library. From these, ten loci were demonstrated to be polymorphic in an Ecuadorian population composed of 27 isolates. The mean number of alleles per locus was 3.2, and the observed mean and expected heterozygosity were 0.03 and 0.43, respectively. The polymorphic microsatellites described herein may be used to study the genetic diversity as well as to comprehend other aspects of M. roreri population biology.